Demolishing “the Dream of Might” of the Nobility of the Polish-Lithuanian Commonwealth, or on the Discussion Concerning the 1670 TV Show - Orzeł, Joanna (Literatura Ludowa. Journal of Folklore and Popular Culture, 2026)
As the screenwriter of 1670, Jakub Rużyłło, admitted, nobody expected such an enormous popularity of this Netflix show. In Poland, it gave rise to intense emotions, both negative and positive, and, as follows, discussions, also among history lovers and professional historians. In their Internet statements (both in the form of articles and comments on social media), some unhappy audience members point to factual errors in the show, others claim that this text slanders the history of the Commonwealth, while others still (who usually do not wonder about the reality of the 17th century society) are amused by 1670. 1670 does contain historical truth, but we are frequently unable to find it, as school education, including Henryk Sienkiewicz’s The Trilogy, shaped an image of the Commonwealth in our minds that is focused on history of events, rather than everyday history; history pertaining to kings, military leaders, and not an average nobleman. And the latter – as the show’s creators depicted in a satirical, sometimes even grotesque manner – was not always a spotless knight, such as Jan Skrzetuski or Michał Wołodyjowski. However, the show’s critics view it through the lens of their own political views, which frequently involve perception of the past, for instance, idealizing the nobility (especially the Hussars) and the Catholic Church.